The cliffs - Cawthon, Scott 1971-; Cooper, Elley; Waggener, Andrea Rains 1960- (Cawthon, Scott 1971- Five nights at Freddy's. Fazbear frights, 2021)
Some things must be learned the hard way . . . Reed sees an opportunity to teach the school bully not to mess with him, but ends up mangling the lesson. Robert, an exhausted single father, gets a crash course in parenting when he buys a fancy new teddy bear to watch and entertain his young son. Chris, eager to join the Science Club at school, agrees to undergo a grisly experiment to be accepted. But in the malevolent universe of Five Nights at Freddy's, there's always an education in pain.